Literatur Review: Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka di Madrasah Ibtidaiyah - Anwar, Zainul; Sukiman, Sukiman (Mitra PGMI: Jurnal Kependidikan MI, 2023)
The independent curriculum is a curriculum that prioritizes learning according to the needs and fulfillment of student competencies. This is in line with differentiated learning which puts forward a learning approach that adapts to the needs of each student in the learning process. However, studies on differentiated implementation in the independent curriculum, especially in MI, are still limited. Departing from these problems, the researcher is interested in conducting a literature review regarding differentiated learning in the implementation of the independent curriculum in MI. The purposes of this research are (1) to describe differentiated learning, (2) to explain the results of implementing differentiated learning in the independent curriculum, especially in MI (3) the challenges of implementing differentiated learning in implementing the independent curriculum in MI. Various literature was obtained from various scientific research from 2021-2023 with the help of Google Scholar and obtained 24 studies with the keywords "differentiated learning" and "independent curriculum". From the 24 articles identification, data selection, due diligence and data analysis were carried out in order to obtain 5 articles that were in accordance with the objectives of the literature review. The results from the literature are 3 core points (1) differentiated learning has four basic aspects namely content, process, project and learning environment; (2) differentiated learning is in line with the objectives of the independent curriculum which emphasizes learning according to students' needs; (3) the challenges that occur in the field are still limited to the skills of teachers and MI resources to implement differentiated learning in MI.